2001
DOI: 10.1200/jco.2001.19.5.1238
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Chemotherapy for Adult Soft Tissue Sarcomas of the Extremities and Girdles: Results of the Italian Randomized Cooperative Trial

Abstract: Intensified adjuvant chemotherapy had a positive impact on the DFS and OS of patients with high-risk extremity soft tissue sarcomas at a median follow-up of 59 months. Therefore, our data favor an intensified treatment in similar cases. Although cure is still difficult to achieve, a significant delay in death is worthwhile, also considering the short duration of treatment and the absence of toxic deaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
348
9
15

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 628 publications
(388 citation statements)
references
References 22 publications
16
348
9
15
Order By: Relevance
“…In our series, the 5-year survival rate of patients who had received adjuvant chemotherapy was 44.45 %. We believe that adjuvant chemotherapy may be useful in the treatment of patients with high-grade RPS [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…In our series, the 5-year survival rate of patients who had received adjuvant chemotherapy was 44.45 %. We believe that adjuvant chemotherapy may be useful in the treatment of patients with high-grade RPS [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20] This novel approach is interesting, but it remains experimental. With re- gard to adjuvant chemotherapy, recent data point to its possible benefit in the treatment of adult STS, provided full doses are employed and high-risk patients are selected: 22,23 If so, then patients with highgrade nonliposarcomas may benefit from chemotherapy for distant metastases. However, this remains to be demonstrated formally.…”
Section: Discussionmentioning
confidence: 99%
“…Novel radiation therapy techniques have been explored, [11][12][13][14][15][16][17][18][19][20][21] and the role of adjuvant chemotherapy still is debated. 22,23 However, efforts to improve treatment results should be based on the patterns in which these tumors currently fail. Thus, the objective of this retrospective analysis was to assess long-term prognosis and patterns of failure in a large cohort of patients with retroperitoneal STS who underwent surgery with curative intent at a single institution over 20 years.…”
mentioning
confidence: 99%
“…One theory regarding how chemotherapy might affect local control is that chemotherapy may affect actively dividing cells at the margins of tumors [19]. Although controversy remains regarding the topic with several articles failing to show an effect on local control [6,7,18], other studies have shown that chemotherapy could benefit patients with sarcoma in terms of better local relapse-free survival and overall survival [9,10,13,21]. The effects could be dependent on the exact agents and dosages.…”
Section: Discussionmentioning
confidence: 99%